Hebella macroplana Watson 2019, sp. nov. - Watson, Jeanette E. (Zenodo, 2019)
Hebella macroplana sp. nov. http://zoobank.org/urn:lsid:zoobank.org:act:CC386770-19A6- 4ACE-8F5C-91F9963120B8 Figure 1f Record. QM G337336. Holotype, one microslide. Coll: eastern Bass Strait, Victoria, 39.552 S, 149.553 E to 39.496 S, 149.598 E, 4197– 4133 m, beam trawl, 23/05/2017. Description . Five stolonal hydrothecae creeping on stem of an antipatharian. Colony entangled with remnants of an unidentifiable anthoathecate hydroid. Hydrorhizal stolon smooth, thin. Pedicel of hydrotheca short, smooth, curved, passing upwards to diaphragm. Hydrothecae tubular, very large, slightly asymmetrical or symmetrical, adcauline side convex to above diaphragm, walls smooth to margin. Diaphragm a barely discernible transverse or slightly oblique ring. Margin circular, slightly everted, one hydrotheca with two widely separated marginal replications. Perisarc very thin, smooth. Remarks . One hydrotheca contains approximately 10 degenerated tentacles indicating that the structure it is not an empty gonotheca. The unsegmented hydrothecal pedicel is very short, and in some hydrothecae it is slightly curved to accommodate the asymmetry of the hydrotheca. The diaphragm varies from a membranous to a thin perisarcal ring. Three genera considered were Hebella, Halisiphonia and Scandia the latter two genera were rejected because they have long hydrothecal pedicels. Hebella macroplana most resembles the Antarctic species Hebella plana Ritchie, 1907; however, the hydrotheca of H. plana is much smaller and has a longer and straighter pedicel [see Totton (1930); Briggs (1938); Boero et al. (1997)]. Although the present material is meagre and without gonothecae, the hydrotheca is extremely large and much bigger than any known species. Etymology . The name alludes to the large hydrotheca compared with that of H. plana. Published as part of Watson, Jeanette E., 2019, Bathyal and abyssal hydroids (Hydrozoa, Leptothecata) from southeastern Australia, pp. 65-72 in Memoirs of Museum Victoria 78 on pages 66-67, DOI:10.24199/j.mmv.2019.78.04, ...